Determining the Local Importance of Non-Timber Forest Products Using Two Different Prioritization Techniques (2012)
Among the key uncertainties in the sustainable management of forest for non-timber forest products (NTFPs) is the high diversity of species and paucity of information on indigenous use pattern. In designing appropriate strategies for sustainable management of non-timber forest products, therefore, it is important to identify species with high local impor-tance with the potential for sustainable and profitable extraction in a managed system. In this study, we assessed the use of two quantitative techniques including the Use-Value index (Phillips and Gentry, 1993) and Assigned-Value approach (Adeola et al., 1994), as procedures for prioritization of NTFP species in a tropical lowland rainforest ecosystem, Omo Forest Reserve (OFR), southwest Nigeria. A simple random sampling approach was employed to obtain data on the uses of NTFP species through semi-structured interview of 81 households in four communities within the reserve. Descriptively, the data were analyzed using frequency distribution, tables, chart and percentages. The Spearman correlation coefficient was employed to test for relationship between the values obtained for each of the two techniques. Results obtained for both techniques were fairly positively correlated (ρ = 0.59; P < 0.01), suggesting a cautious interchangeable use of the techniques for the same end. Based on our findings, we posit that in evaluating forest and NTFPs for local importance and use, the end objectives of such evaluation must be critically examined in the light of the interest of the different respondents’ group.